Of women and salt ebook A novel. - Garcia, Gabriela (2021)
AN INSTANT NEW YORK TIMES BESTSELLER THE WASHINGTON POST NOTABLE BOOK OF 2021 A GOOD MORNING AMERICA BOOK CLUB PICK WINNER of the Isabel Allende Most Inspirational Fiction Award - International Latino Book Awards WINNER of Best Literary Fiction - She Reads Best of 2021 Awards FINALIST for the 2022 Southern Book Prize LONGLISTED for Crook's Corner Book Prize NOMINEE for 2021 Goodreads Choice Award in Debut Novel and Historical Fiction A sweeping, masterful debut about a daughter's fateful choice, a mother motivated by her own past, and a family legacy that begins in Cuba before either of them were born In present-day Miami, Jeanette is battling addiction. Daughter of Carmen, a Cuban immigrant, she is determined to learn more about her family history from her reticent mother and makes the snap decision to take in the daughter of a neighbor detained by ICE. Carmen, still wrestling with the trauma of displacement, must process her difficult relationship with her own mother while trying to raise a wayward Jeanette. Steadfast in her quest for understanding, Jeanette travels to Cuba to see her grandmother and reckon with secrets from the past destined to erupt. From 19th-century cigar factories to present-day detention centers, from Cuba to Mexico, Gabriela Garcia's Of Women and Salt is a kaleidoscopic portrait of betrayals—personal and political, self-inflicted and those done by others—that have shaped the lives of these extraordinary women. A haunting meditation on the choices of mothers, the legacy of the memories they carry, and the tenacity of women who choose to tell their stories despite those who wish to silence them, this is more than a diaspora story; it is a story of America's most tangled, honest, human roots.